Implementation of Kepmen ESDM No 1827 K/30/MEM/2018 Concerning Guidelines for the Implementation of Good Mining Techniques for the Utilization of Coal Post-Mining Reclamation in the Form of Tourism - Meily Putri Amelia; Suhadi; Pujiono (Dinasti Research, 2025)
Indonesia's natural resource wealth has been recognized by the world since the colonial period, one of its natural wealth is mineral resources. The abundance of mineral mining goods in Indonesia creates another urgency regarding the final production results from mining, namely mine excavation holes. The solution offered by the government is reclamation in the form of other forms of utilization, one of which is tourism. This solution was realized with Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM/2018 concerning guidelines for good mining engineering principles. The use of reclamation as a form of tourism has had an impact on the environment, social and economy, for example the AirANGKAng Tourism Village where tourist attractions include fisheries, animal husbandry, water tourism, and animal conservation, the Breksi Cliff Tourism in Jogjakarta, then the Lati Petangis Grand Forest Park in Paser where it is used as a means of water tourism, flora and fauna conservation, and is used for deer farming.